(untitled) (Indian Journal of Arid Horticulture, 2025)
Indian rock phosphate are of low grade and usually not suitable for the manufacture of phosphatic fertilizer (Manna et al., 2003). Phosphocompost prepared by composting organic wastes with different graded dose of Missouri rock phosphate @ 1, 4 and 8% of substrate, was reported to be comparable to single super phosphate in its effect on yield and phosphorus uptake in crops (Mishra et al. 1982, Banga et al. 1985). India has large deposit of rock phosphate but only 30% of it is in use. Direct application of rock phosphate has given good response in acid soil (Waigwa et al. 2003) but no effect in natural and alkaline soil (Hundal and Sekhon 1976, Rahman and Hajra, 2003). Mathur et al. (1980) observed that citrate soluble phosphorus content was increased on composting of Missouri rock. The P use efficiency is low as the water- soluble phosphate when applied to soil is quickly converted into unavailable forms by precipitation or adsorption with AV Fe in acidic (Chakravarti and Talibudeen 1962) and with Ca in alkaline condition. On the contrary organic forms of phosphorus immobilized in microbial cells are mineralized slowly (Dinesh et al, 2002) and made available to the plant regularly for a longer period increasing the P- use efficiency significantly. An attempt was made in the present study to quantify the quality improvement of compost by P enrichment through rock phosphate at different doses with decomposable organic matter during composting.